2016
DOI: 10.1109/tap.2016.2583507
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Path Loss Models for Wireless Sensor Network Deployments in Short and Tall Natural Grass Environments

Abstract: Extensive research has not been done on propagation modeling for natural short-and tall-grass environments for the purpose of wireless sensor deployment. This study is essential for efficiently deploying wireless sensors in different applications such as tracking the grazing habits of cows on the grass or monitoring sporting activities. This study proposes empirical path loss models for wireless sensor deployments in grass environments. The proposed models are compared with theoretical models to demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…There exist different approaches to predict the path-loss. A number of empirical models for path-loss were derived based on field measurements in various environments [6]- [8]. The measurement campaigns required for deriving these models usually mean a lot of cost in time and manpower.…”
Section: Introductionmentioning
confidence: 99%
“…There exist different approaches to predict the path-loss. A number of empirical models for path-loss were derived based on field measurements in various environments [6]- [8]. The measurement campaigns required for deriving these models usually mean a lot of cost in time and manpower.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, six different propagation models that cover various types of terrains are employed. Each terrain propagation model was measured with different heights [4]. This research investigates three types of terrains: short grass, tall grass, and dense trees with different heights.…”
Section: Empirical Propagation Modelmentioning
confidence: 99%
“…Using empirical propagation models, this research aims to study the effects of the deployment environment on WSN performance. Empirical propagation models of tall grass, short grass, and dense trees are used to estimate deployment coverage, connectivity, network lifetime and throughput [4]. This paper presents a realistic decision-making methodology for stochastic and deterministic deployments of WSN.…”
Section: Introductionmentioning
confidence: 99%
“…Parameters L(d 0 ) and n can be estimated by performing linear regression with the measurement data. While σ(dB) may be determined from experimental data using [2] …”
Section: A Path Loss Modelsmentioning
confidence: 99%
“…Near-ground path loss radio frequency (RF) measurements on a tarmac surface similar to that of a roads is reported in [1]. Empirical path loss models for WSN deployments in short and tall natural grass and forest environments are reported in [2] and [3], respectively. Denis et al [4] reported ultra wideband (UWB) measurement results and path loss modeling for snowy environments for rescue and monitoring of snow avalanche victim applications.…”
mentioning
confidence: 99%